The Place of Politics in I. Kant’s Structure of Pure Reason - Jokubaitis, Alvydas (Politologija, 2023)
Kant’s political philosophy is usually seen as a coherent part of his philosophical system. However, politics is not an integral part of his conception of pure reason. The aim of the article is to find the place of politics in Kant’s structure of pure reason. The paper attempts to provide an answer to the question why Kant did not undertake an investigation of politics as a part of his analysis of the structure of pure reason. It is argued that the central place of the problem of metaphysics was the cause behind this neglect. Transcendental dialectic in Critique of Pure Reason is the place where for the first time principles of the analysis of political ideas are presented. However, Kant did not see that with his transcendental dialectics he entered the realm of politics, he did not put forward an analysis of the nature of political ideas. The place of politics in Kant’s structure of pure reason can be determined by paying close attention to three main factors – conception of transcendental ideas, the primacy of practical reason and aesthetic ideas. Kant did not provide a unified account of these three elements, which are necessary to understand the place of politics in the structure of pure reason.